Double cytoplast embryonic cloning improves in vitro but not in vivo development from mitotic pluripotent cells in cattle - Appleby, Sarah Jane; Misica‐Turner, Pavla; Oback, Fleur Catherine; Dhali, Arindam; McLean, Zachariah Louis; Oback, Björn (Frontiers in Genetics, 2022)
Cloning multiple animals from genomically selected donor embryos is inefficient but would accelerate genetic gain in dairy cattle breeding. To improve embryo cloning efficiency, we explored the idea that epigenetic reprogramming improves when donor cells are in mitosis. We derived primary cultures from bovine inner cell mass (ICM) cells of in vitro fertilised (IVF) embryos. Cells were grown feeder-free in chemically defined medium with increased double kinase inhibition (‘2i+). Adding recombinant bovine interleukin 6 to 2i+ medium improved plating efficiency, outgrowth expansion and expression of pluripotency-associated epiblast marker genes (NANOG, FGF4, SOX2, DPPA3). For genotype multiplication by embryonic cell transfer (ECT) cloning, primary colonies were treated with nocodazole, and single mitotic donors harvested by mechanical shake-off. Immunofluorescence against phosphorylated histone 3 (P-H3) showed 40% of nocodazole-treated cells in metaphase compared to 11% in DMSO controls (P<1x10-5), with an average 53% of P-H3-positive cells expressing the pluripotency marker SOX2. We optimised several parameters (fusion buffer, pronase treatment, activation timing) for ECT with mitotic embryonic donors. Serial double cytoplast ECT, whereby another cytoplast was fused to the first cloned reconstruct, doubled cloned blastocyst development and improved morphological embryo quality. However, in situ karyotyping revealed that over 90% of mitotic ECT-derived blastocysts were tetraploid or aneuploid with extra chromosomes, compared to less than 2% in the original ICM donor cells. Following transfer of single vs double cytoplast embryos, there was no difference between the two methods in pregnancy establishment at D35 (1/22=5% vs 4/53=8% for single vs double ECT, respectively). Overall, post-implantation development was drastically reduced from embryonic mitotic clones compared to somatic interphase clones and IVF controls. We conclude that mitotic donors cause ploidy errors during in vitro development that cannot be rescued by enhanced epigenetic reprogramming through serial cloning.